KONSTRUKSI IRASIONAL DALAM BERITA HOAKS DI MEDIA SOSIAL - Muh Yusran; Sultan; Usman (Journal Studies in Indonesian Language and Literature, 2024)
This research aims to describe the form of accentuation fallacy, the form of amphibole fallacy, the form of amphibole fallacy , The form of metaphorical fallacy. This research uses descriptive qualitative research. The focus in this research is the form of accentuation, amphibole, equivocation and metaphorical errors. The data collection technique in this research was carried out in three stages, namely; observation, documentation, and reading and taking notes. The research instrument used in this research is a researcher who acts as a human instrument. The results of this research show that the form of accentuation error in this research is in the form of words. The form of amphibious error is in the form of words and sentences. The form of equivocation fallacy is in the form of words. Metaphorical fallacy takes the form of words and phrases.